Republic of Serbia : Financial Sector Assessment Program Update; Detailed Assessment of Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper discusses key findings of the Detailed Assessment of Basel Core Principles (BCPs) for Effective Banking Supervision on the Republic of Serbia. The assessment reveals that Serbia has made considerable progress toward enhanced compliance with the BCPs and with international standards. A major overhaul of the legal framework-the enactment of the new laws on banks in 2005 and the issuance of new regulations-has provided the basis for this improvement, which are reflected in upgraded scores for a considerable number of BCPs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet